Severity of Hydrological Drought in the Lui River Basin, Hulu Langat, Selangor - Nordin Sakke; Hamirdin Ithnin; Azali Saudi; Mohammad Tahir Mapa (Penerbit Universiti Pendidikan Sultan Idris, 2016)
Hydrological drought is a phenomenon of extreme water shortage that have an impact on human life. The impact of the drought depends on the severity of a drought. The severity of hydrological drought events can be described through a period of drought or total deficit. Long periods of drought and high amount of water deficit are important indicators of the extreme drought. Therefore, this article attempts to look at the severity of the drought in Lui River, Hulu Langat, Selangor. In the context of this study, the overrun (percentile - Q) than the flow duration curve (FDC) is used to determine the drought. 48 years of discharge data for Lui station was used to determine the value of Q. Using percentile Q70 = 1.15 m3 s -1 as the threshold level (TL) drought base obtained from FDC, available discharge duration and the amount of the deficit resulting vary according to grade of the drought severity. Based on the analysis, the cumulative period of drought was 2061 days at PAQ70, 1742 days at PAQ80, 542 days at PAQ90 and 204 days at PAQ95. The longest period of drought events recorded in 1989, namely 250 days. In terms of cumulative deficit, a total of 1183 m3 s -1 recorded at PAQ70, 598 m3 s -1 at PAQ80, 116 m3 s -1 at PAQ90 and 30 m3 s -1 at PAQ95. The highest deficit was recorded in 2001 (148 m3 s-1). Form these figures, 49.5% were categorized as Normal Drought (Q70 - Q79.9), 40.7% are categorized as Slight Drought (Q80 - Q89.9), 7.3% were categorized Moderate Drought (Q90 - Q94.9) and the remaining 2.5% is classified Severe (Q95 and above).